What doesn't kill you [large type] - Johansen, Iris (Thorndike Press large print basic series., 2012)
Catherine Ling was abandoned in the streets of Hong Kong at the age of four, and was schooled in the art of survival. As a teenager, she came under the tutelage of the mysterious Hu Chang - a skilled assassin and master poisoner. As a young woman, she was recruited by the CIA and is now one of their most effective operatives. Then her old friend Hu Chang creates something deadly and completely untraceable - and the chase is on to be the first to get it.